Analisis Strategi Pengembang Bisnis Berbasis Syari’ah Pasca Covid-19 Studi Kasus Rumah Makan Padang Famili Sakato - Krisandi, Rahmat (Sahabat Publikasi, 2023)
The purpose of this research is to find out the strategy for developing the Padang Famili Sakato restaurant business after Covid-19. This study uses a descriptive qualitative method by looking at the phenomena that exist in the field. The data used are primary data and secondary data. By collecting data using observation and interview techniques. From the results of the study it was concluded that in order to run a post-covid-19 Padang restaurant business, there needs to be a strategy carried out by Muslim entrepreneurs in developing their business better. These strategies are as follows: 1) strategy in product supply. 2) strategy in determining the right price and following 3) determining the strategic location and also in the distribution of attractive product.